Inflammatory bowel disease in pregnancy. Issue 2 (1st February 2003) - Alstead, E M; Nelson-Piercy, C
Abstract : Women and men with inflammatory bowel disease (IBD) frequently express concerns about fertility and pregnancy. The evidence suggests that women with IBD can expect to have a normal pregnancy outcome provided they have inactive disease. They have an increased risk of having a small or premature baby but the majority will have a normal outcome of pregnancy. The commonly used drugs appear to be safe and well tolerated in pregnancy. There remains a need for further studies in this area to help in the difficult decisions about the management of IBD around the time of conception and during pregnancy.